Cost-effectiveness estimates of vaccination against rotavirus in Piedmont, Italy - Maria R. Gualano; Robin Thomas; Renata Gili; Giacomo Scaioli; Gianluca Voglino; Carla Zotti (Elsevier, 2018)
Background: Rotavirus-induced gastroenteritis (RVGE) represents the most frequent form of severe gastroenteritis in children. In such a scenario, the availability of an efficient anti-Rotavirus (anti-RV) vaccine represents an effective prevention tool able to prevent those complications mainly linked to the moderate-severe forms of this disease, which require hospital care. The aim of the present study is to estimate the cost effectiveness of universal routine infant RV vaccination program and its budget impact on the Regional Health Service (RHS) of Piedmont, Italy, in order to evaluate the opportunity of the implementation of a national anti-Rotavirus vaccination programme. Methods: The researchers performed a cost-effectiveness analysis comparing costs and benefits of a Rotarix two-dose vaccination versus non vaccination and a budget impact analysis (BIA), complementary to the cost-effectiveness analysis. Results: Our results show that the mass implementation of an anti-RV vaccination in Piedmont, in addition to the expected public health benefits, also allows the RHS to save a considerable amount of money within a short period of time, due to the remarkable reduction of direct health costs associated with RVGE management. In fact, as the analysis shows, a universal vaccination against RV results in money-saving for the RHS already from the 2nd year (with a vaccination coverage of 50%). During the five year period, the active and free offer of the anti-RV vaccination would determine a total saving for RHS of about € 503.000. The cost-effectiveness analysis results showed a cost-saving ICER (incremental cost-effectiveness ratio) relevant to the RHS and equal to - €12.197/QALY. Conclusion: In conclusion the adoption of a universal preventive strategy for all the infants in the Piedmont Region may contribute significantly towards the control of RVGE incidence, thus allowing a noteworthy saving of economic and social resources for both the RHS and the general public. Keywords: Rotavirus, Cost-effectiveness, Economic analysis, Burden of disease, Vaccine